Factors determining the occurrence and spatial association of meso-carnivores in the semi-arid landscape of Madhya Pradesh, India - Sharma, Shantanu; Panda, Debashish; Jain, Akshay; Rajaraman, Rajasekar; Maurya, Kamlesh K.; Singh, Randeep (Mammal research, 2026)
Understanding how mesocarnivores survive in human-modified landscapes is important for making their conservation planning and sustaining their ecological roles in multi-use systems. Their relatively small size, broad diets, and rapid reproduction often enable them to adapt well to anthropogenic environments. We assessed habitat use and spatial associations of four mesocarnivores—golden jackal ( Canis aureus ), Indian fox ( Vulpes bengalensis ), jungle cat ( Felis chaus ), and ratel ( Mellivora capensis )—in the Chambal ravines of Madhya Pradesh, India, using single-season occupancy and Generalized Linear Models (GLM) that incorporated ecological and anthropogenic variables. To explore interspecific interactions, data were also collected on leopard, hyena, and feral dog. We found that naïve occupancy was highest for golden jackal (1.0), followed by Indian fox (0.49), jungle cat (0.42), and ratel (0.25). Mean detection probabilities were 0.382 ± 0.01 for jackal, 0.088 ± 0.01 for fox, 0.082 ± 0.01 for jungle cat, and 0.05 ± 0.01 for ratel. Model-averaged site-use probabilities were Ψ = 1.00 for jackal, Ψ = 0.63 ± 0.10 for fox, Ψ = 0.76 ± 0.11 for jungle cat, and Ψ = 0.52 ± 0.15 for ratel. Our results suggest golden jackals, being generalists, preferred flat scrublands near villages, relying on human-related food like livestock carcasses, while avoiding rugged areas. Indian foxes preferred scrublands farther from roads and farms. Jungle cats occurred near villages and in rugged areas, likely due to rodent availability. Ratels selected densely vegetated zones with high NDVI and scrub cover, mainly in protected forests. Despite differences in body size and diet, mesocarnivores showed positive spatial associations, supported by the landscape’s resource heterogeneity. Interactions with leopards and hyenas were mostly neutral or positive, except for jackals, which were negatively associated with leopards. Feral dogs showed mostly positive but non-significant associations. The study underscores the influence of human infrastructure, viz., roads and villages, on mesocarnivore presence and highlights the need for targeted conservation in the ravines.